The Dome and the Rock Structure in the Poetry of Wallace Stevens - Baird, James (Johns Hopkins University Press, 2020)
Originally published in 1968. In The Dome and the Rock: Structure in the Poetry of Wallace Stevens, James Baird traces the process of Wallace Steven's Grand Poem and the total structure that it accomplished in language. In the words of Professor Baird, "The full art of Stevens is organized with architectural precision. The shape of the mind becomes a building, the framework of which is founded in a willed symmetry of design." In The Dome and the Rock, James Baird exposes the capacity of Wallace Stevens to design his poetry in a manner similar to an architect, and he "reveals the craftsmanship of [Wallace's] acts as builder."